Natural and Man-made Evolution of Sustainability of Cotton Production and Processing over the Centuries in the World - Narayanan, S. S.; Maiti, Ratikanta; Vidyasagar, Parchuri (International Journal of Bio-resource and Stress Management, 2023)
Cotton is a premier textile fiber and one of the most competitive crops in global agriculture. Though primarily considered as fiber crop cotton is also an important source of oilseed and livestock feed besides providing several other by-products. In fact all parts of the cotton plant are used. Cotton is in harmony with the environment today than ever before. Invention of gin, development of Bt-cotton, etc. are man-made evolution which helped cotton to sustain productivity and global competitiveness. The success story of cotton is that of natural and man-made evolution of sustainability of cotton production and processing over the centuries in the world. The article provides a fascinating glimpse into the evolution and sustainability of cotton crop over the centuries around the world.